Organizational culture mapping analysis through Organizational Culture Assessment (OCA) - Kartika Mega Tama (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Organization is characterized by the different senses of culture and uniqueness that distinguish one’s entity from others. Culture plays an important role in organization as a good culture can provide organization support to achieve goals. Organizational culture acts as a guideline for an individual’s daily behavior that will influence the decision-making process and provide direction for leaders and members to achieve organizational goals. In its creation, organizational culture was built according to organization circumstances. Organizational culture has important roles in the maintenance and development of the organization’s vision and mission. Organizational culture is an essential tool in the improvement of organizational performance and member capability. Therefore, there is an need for the Karawitan Dance Activity Unit (UKTK) of Universitas Airlangga to project the state of the existing and expected culture of the organization. By conducting cultural mapping, existing visions and missions of an organization can be transformed. Organizational culture was measured by the Organizational Culture Assessment (OCA) method. The measurement is held by distributing instruments and contains 20 questions. The questionnaire was distributed to both leaders and members of the UKTK Airlangga University and its aim was to identify the expected culture of the university relative to the reality of culture. The results of the questionnaire showed that respondents felt the culture at the UKTK is of a mechanistic nature. Similarly, the expected culture of the UKTK is of a mechanistic nature. The compatibility between cultural reality and expectations in the UKTK supports organizational goals. This situation can generate good relationships between the leaders and members of the UKTK Airlangga University which results in harmony throughout the organization. The existing mechanistic organizational culture can be seen as a strategy by which to achieve the objectives of the UKTK in Airlangga University. The results of the study can also strengthen the organizational culture as it can be a powerful means by which to control and increase the consistent behavior of members of the organization. In addition, the awareness of the existing organizational culture can facilitate the implementation of work programs agreed upon by the UKTK organization of Airlangga University.